Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration - Rodriguez-Calcerrada, Jesus; Limousin, Jean-Marc; Martin-StPaul, Nicolas K; Jaeger, Carsten; Rambal, Serge (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020
Keywords: carbon budget; ecosystem respiration; leaf life span; resource remobilization; soluble sugars; temperature sensitivity

Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species - Gratani, L; Varone, L (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.
Keywords: dry mass; Erica; leaf life span; Leaf mass per area; Phillyrea; Pistacia; Quercus; RAINFALL; Rosmarinus.

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, a; Mediavilla, S (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, A.; Mediavilla, S. (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species - Mediavilla, S; Escudero, a (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.
Keywords: Leaf growth; leaf life span; mean residence time; nitrogen; phosphorus

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species - Mediavilla, S.; Escudero, A. (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Leaf growth; leaf life span; mean residence time; nitrogen; phosphorus

Forecasted stability of Mediterranean evergreen species considering global changes - Gratani, L; Bombelli, A (GLOBAL CHANGE AND PROTECTED AREAS, 2001)
Plant communities of the Mediterranean climate Regions are exposed to high temperatures, high radiation and water stress during summer, they are dominated by evergreen sclerophyllous species and drought semi deciduous species. To define the adaptive strategies, anatomical and morphological leaf traits of Quercus ilex L., Phillyrea latifolia L. (typical evergreen sclerophyllous species) and Cistus incanus L., (a drought semi deciduous species), growing in the Mediterranean maquis along Pome's coast line (Italy) were analysed. The typical evergreen sclerophyllous species have long leaf life span (from 1 to 4 years), steeper leaf inclination (average 56 degrees), higher specific leaf mass (average 21.3 mg cm(-2)) and the highest leaf thickness (average 324 mum). The semi deciduous species have a lower leaf life span (from 4 to 8 months), a lower leaf inclination (44 degrees +/- 13 degrees), a lower specific leaf mass (14.7 +/-1.5 mg cm(-2)) and a lower leaf thickness (244 +/- 15 mum). The more xeromorphyc species (Q. ilex and P. latifolia) may be at a competitive advantage considering the forecasted air temperature increase in the Mediterranean basin. Increasing drought stress may in fact determine a shortening of leaf life span that may prove to be critical for C. incanus. Knowledge of plant response to stress factors is important in the perspective of climatic changes.
Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999
Keywords: C. incanus; leaf life span; P. latifolia; Q. ilex